At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga.
Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus.
Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get our expert's

answer on brainly

SEE EXPERT ANSWER

Get your **free** account and access **expert** answers to this and **thousands** of other questions.

I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your **free** account and access **expert** answers to this and **thousands** of other questions

multiply with 6 and 7 than bring x to one side. voila

7x/42 - 6x/42 = 5
x/42=5
x=5(42)

so step 2 would look like x/7-x/6=5

yes

Then you make the denominators the same

which would be 42,

yes since 6 X 7 = 42

this is the part i get confused at

would it look like x/42?

ahhh ok

so then is x/42=5

Yup

and then simplify from there

yup :)

how do i get x by itself?

move the 42 over to the other side by timesing both sides by 42.

|dw:1349349298325:dw|

42(x/42) = 5(42)
x =210

thank you so much.. fractions is one thing i have an issue with..

that's fine :)

i have even harder ones... like \[\frac{ x}{ 2x+2 }=\frac{ -2x }{ 4x+4 }+\frac{ 2x-3 }{ x+1 }\]

\[{-2x \over 4(x+1)} + {4(2x-3) \over 4(x+1)}\]

and add them
\[-2x + 8x -12 \over 4(x+1)\]

do the same with the other side and use 2(x+1) as denominator

\[{x \over 2(x+1)} = {6x -12 \over 4(x+1)}\]

and cross multiply for simplification

2x(x+1) = (6x-12) (x+1)

cancel the x+1
and you have 2x = 6x-12

and that is simplified as
-4x = -12
which means x = 3

understand?

i believe so

great :)

i have one more fraction if anyone is interested in helping

\[\frac{ 5 }{ y-4 }-\frac{ 8 }{ y-4 }=\frac{ 2 }{ y^2-16 }\]

it throws me off to add sqrt

Then knock off the y-4 so you're left with
\[-3 = {2 \over y+4}\]

and then use -3 (y+4) = 2
and simplify
-3y - 12 = 2
-3y = 2 +12
-3y = 14
y = 14/-3

y = -(14/3)

wow that was easier than i thought

You were only stumped by the y^2 - 16
which is simplified as (y-4)(y+4)

thank you so much for helping me with these!

No probelma :)